Cu-BTC metal-organic framework as a novel catalyst for low temperature selective catalytic reduction (SCR) of NO by NH3: Promotional effect of activation temperature. Issue 172 (12th June 2016) - Li, Chunyan; Shi, Yong; Zhang, Hao; Zhao, Qidong; Xue, Fanghong; Li, Xinyong
Abstract: Metal-organic framework Cu-BTC was synthesized by hydrothermal method, and was employed as denitrification catalyst for low temperature selective catalytic reduction of NO with NH3 (NH3 -SCR). After activated at different temperatures from 180°C to 250°C in vacuum, Cu-BTC samples were characterized by NH3 -SCR test, X-ray powder diffraction, thermal analysis, scanning electron microscope and in situ Fourier-transform infrared. NO conversion results revealed that activation temperatures played a significant beneficial effect role in Cu-BTC catalytic performance for low-temperature NH3 -SCR reaction. The Cu-BTC catalyst pre-treated at 230°C achieved a complete NO conversion efficiency with large operating-temperature window from 220°C to 280°C. This excellent catalytic activity was mainly attributed to the unsaturated Cu sites in Cu-BTC. The correlation between catalytic property and structure of Cu-BTC was discussed.